Sintesis biodiesel dengan teknik ozonasi: investigasi produk ozonida etil-ester minyak kelapa dan minyak kedelai - Setijo Bismo; L Linda; Sofia Loren Butarbutar (Jurnal Teknik Kimia Indonesia, 2005)
Similarly with other alkyl-ester biodisesls, coconut oil and soybean oil ethyl-ester (COEE and SOEE) still retain some disadvantages to apply directly or used as diesel fuel additives, such as high viscosity and low ignition performance. The main objective of the reasearch is to introduce an alternative process to improve such drawbacks, that is to convert a small portion of ethyl-ester to ozonide compounds. The ozonolysis of ethyl-esters. whether catalytic or non-catalytic processes, generally yields ozonides, carboxylic acids, and hydrocarbons with shorter carbon chain, e.g. aldehyde and ketone to improve their fuel characteristics. The main problem of such ozonolysis is the effectiveness of the ozonation process itself Such a preliminary investigation of COEE and SOEE ozonation process to ozonides or other compounds, the presented results are the examination of main parameters such as, viscosity, density,  total acid number, water content,  and cetane index. The changes in the ethyl esters'physical and chemical properties werefound to be: an increased in their viscosity, total acid number, and cetane index, and also a decreased in their density and water content. The visible change after ozonation process was the odor ofthe esters. These parameters changes was an indicator that new substances have been producedfrom  the ozonation of ethyl esters.Keywords: Coconut Oil, Soyabean Oil, Biodiesel, Methyl Ester, Ethyl Ester, Ozonide, OzonolysisAbstrakBiodiesel etil-ester minyak kelapa dan kedelai, seperti juga alkif-ester lainnya, memiliki beberapa kelemahan bila digunakan langsung atau sebagai aditif bahan bakar mesin diesel, seperti viskositas yang tinggi dan sifat penyalaannya yang kurang baik. Tujuan utama dari penelitian ini adalah mencari proses alternatif untuk memperbaiki kekurangan-kekurangan tersebut, yaitu mengkonversi sebagian etil-ester menjadi senyawa ozonida. Reaksi ozonolisis alkil-ester, baik katalitik maupun non-katalitik, menghasilkan senyawa-senyawa ozonida, asam karboksilat, dan senyawa-senyawa hidrokarbon yang lebih pendek rantai karbonnya, seperti aldehida dan keton sehingga dapat meningkatkan karakteristiknya sebagai bahan bakar. Kendala utama dalam konversi tersebut adalah efektifltas dari reaksi ozonasi itu sendiri. Sebagai investigasi awal dari reaksi ozonasi etil-ester minyak kelapa dan kedelai menjadi senyawa ozonida dan senyawa-senyawa lainnya, disajikqn hasi hasill pengujian parameter-parameter utama, seperti viskositas, densitas, bilangan asam, kadar air dan indeks setana. Perubahan sifat-sifat fisika dan kimiawi yang dht}i setelah mengalami proses ozonasi adalah: kenaikan viskositas, bilangan asam, dan indeks setana, serta penurunan densitas dan kadar air. Sedangkan perubahan yang dapat diamati langsung adalah perubahan aromalbau dari etil-ester kedelai dan kelapa setelah mengalami proses ozonasi. Perubahan parameter-parameter yang diuji ini menandakan telah terbentuknya senyawa baru akibat reaksi etil-ester dengan ozon.Kata Kunci: Minyak Kelapa, Minyak Kedelai, Biodiesel, Metil-ester, Etil-ester, Ozonida, OzonolisisSimilarlywithotheralkyl-esterbiodisesls,coconutoilandsoybeanoilethyl-ester(COEEandSOEE)stillretainsomedisadvantagestoapplydirectlyorusedasdieselfueladditives,suchashighviscosityandlowignitionperformance.Themainobjectiveofthereasearchistointroduceanalternative processtoimprovesuch drawbacks,thatistoconvertasmallportionofethyl-estertoozonidecompounds.Theozonolysisofethyl-esters.whethercatalyticornon-catalyticprocesses,generallyyieldsozonides,carboxylicacids,andhydrocarbonswithshortercarbonchain,e.g.aldehydeand ketonetoimprovetheirfue/characteristics.ThemainproblemofsuchozonolysisistheeffectivenessoftheozonationprocessitselfSuchapreliminaryinvestigationofCOEEandSOEEozonationprocesstoozonidesorothercompounds,thepresentedresultsaretheexaminationofmainparameterssuchas,viscosity,density,  totalacidnumber,watercontent,  andcetaneindex.Thechangesintheethylesters'physicalandchemicalpropertieswerefoundtobe:anincreasedintheir viscosity,totalacidnumber,andcetaneindex,andalsoadecreasedintheirdensityandwatercontent. Thevisiblechangeafterozonationprocesswas theodorofthe esters.Theseparameterschangeswas anindicatorthatnewsubstanceshavebeenproducedfrom  theozonationofethylesters. Keywords:CoconutOil, SoyabeanOil,Biodiesel,MethylEster,EthylEster,Ozonide, Ozonolysis